Study of Earth atmosphere components by Laser Spectroscopy (Latakia University Journal -Basic Sciences Series, 2019)
The aim of this work is to measure concentration of some atmosphere components(CO2, NH3, O3, CH4) by using TDLAS (Tunable Diode Laser Absorption Spectroscopy)under different pressure (1 atm,100 mbar,72.5 mbar,50mbar,10mbar). This work had doneby using HITRAN (HIgh Resolution TRANsmission molecular absorption data base)database to define the density of spectral line and define the present gas by knowing thewavenumber where absorption was happened, then  concentration of each gas in the samplehas been calculated by using optic path length inside the  multi reflections cell, deferentpressure and intensity of spectral line.This system was considered as LIDAR (Light Detection And Ringing) in- situe for gasdetection and concentration measuring.